International human rights standards versus cultural practices: a case against harmful cultural practices in Sub-Saharan Africa, with a specific reference to FGM - Santino Ayuel Longar Dau (Discover Global Society, 2024)
Abstract One of the major limitations of the cultural relativist contention is its property to rank group rights above and beyond individual rights. This paper, however, contends that such a postulation is utilitarian in character. It suggests that what is good for the many is conclusive as to the justness of an outcome. The paper further underscores that IHRs regime must be seen as an indivisible structure of interconnected sets of rights and freedoms within which the significance of each right and/or freedom is augmented or guaranteed by the synchronous protection of all other rights and/or freedoms. This proposition is pertinent to the enduring tension between IHRs standards and cultural practices in the African debate on human rights. Indeed, when juxtaposed against IHRs standards, certain cultural practices are evidently inimical to the inherent human dignity, contrary to the universal vision for the human rights regime. It stands to reason that, in the event of an irreconcilable friction between individual and group rights, the former must supersede the latter. The paper concludes that the long-standing normativity of specific traditional or cultural practices cannot plausibly be invoked as a defense for the continuation of harmful cultural practices, such as FGM, considering that such practices hardly ever  fall within the meaning of the group right to culture under IHRL and are, therefore, pernicious to the IHRs standards as culturally constituted.